Effective Communication In Rural Bureaucratic Practices (Study on the Government of Padang Capo Ilir Village, Lubuk Sandi Sub-District, Seluma Regency, Bengkulu Province) - Diyan Putra; Sri Narti; Bayu Risdiyanto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to describe how the effective communication of the head of Padang Capo Ilir Village, Lubuk Sandi Sub-District, Seluma Regency in the practice of rural bureaucracy. This study used qualitative research methods. Data collection techniques were carried out using observation, interview and documentation techniques. This study used Effective Communication Theory according to Prijosaksono et al (2002), namely: Respect, Empathy, Audible, Clarity and Humble. Based on the theory used in this research, the research results are obtained: When solving a problem that arises, the head of Padang Capo Ilir Village, Lubuk Sandi Sub-District, Seluma Regency in the Practice of Rural Bureaucracy uses the deliberative method in finding the best solution. The communication that exists between the Head of Padang Capo Ilir Village, Lubuk Sandi Sub-District, Seluma Regency, with Village Officials and the community has been quite well established. This is indicated by the few complaints received, so it can be interpreted that the community is quite satisfied with the services provided by the Village Head and related Village Officials.